2015
DOI: 10.14309/crj.2015.62
|View full text |Cite
|
Sign up to set email alerts
|

Esophagogastric Fistula Caused by an Angelchik Antireflux Prosthesis

Abstract: The Angelchik prosthesis is an antireflux device that was popular in the 1980s for treatment of refractory gastroesophageal reflux disease (GERD). We present a patient who developed a gastroesophageal fistula 17 years after Angelchik prosthesis placement. The incidence of late complications continues to grow, and clinicians should consider device malfunction in patients with history of Angelchik placement presenting with abdominal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This fibrous capsule was seen intraoperatively in our patient during the removal of the AD. Other reported complications included migration of the device, erosion through the oesophagus, fistula formation and the development of adenocarcinoma proximal to the AD 7 8 10 11. Specifically, our patient developed end-stage oesophageal disease with a complete inability to swallow, necessitating the placement of a J-tube to allow for enteral nutritional support.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This fibrous capsule was seen intraoperatively in our patient during the removal of the AD. Other reported complications included migration of the device, erosion through the oesophagus, fistula formation and the development of adenocarcinoma proximal to the AD 7 8 10 11. Specifically, our patient developed end-stage oesophageal disease with a complete inability to swallow, necessitating the placement of a J-tube to allow for enteral nutritional support.…”
Section: Discussionmentioning
confidence: 89%
“…Jalil et al 14 described the laparoscopic removal of Angelchik prosthesis followed by an immediate Nissen’s fundoplication in a patient who had an AD for over 20 years 14. Others have demonstrated successful endoscopic removal of AD that had eroded through the oesophagus or created a fistula 8 11. Fewer reports, however, have demonstrated the removal of AD via a thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
“…12 Pence et al presented a patient who developed fistula 17 years after Angelchik prosthesis placement for refractory GERD. 17 Surgically induced ischemia and subsequent tissue necrosis, microscopic perforations, local ischemia, and stitch abscess may be contributing factors after a fundoplication procedure. 11,20,25 Another possibility is an iatrogenic fistula due to full-thickness suture, nasogastric tube trauma, 16,21,22 or dilation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about possible complications and erosion of a foreign body placed at the gastroesophageal junction (GEJ) led to initial criticism because the past experience with the Angelchick and gastric banding devices [8,9]. Previously published studies demonstrated that the rate of MSA removal ranges from 1.1 to 6.7% [11][12][13].…”
Section: Introductionmentioning
confidence: 99%